Expression of receptors for advanced glycosylated end-products in renal disease - Abel, Marcus; Ritthaler, Ute Maria; Zhang, Y.; Deng, Youhua; Schmidt, A. M.; Greten, Henry Johannes; Sernau, Torsten; Wahl, Peter; Andrassy, Konrad; Ritz, Eberhard; Waldherr, Rüdiger; Stern, David Mark; et al. (Nephrology, dialysis, transplantation, 1995)
Methods. RAGE was detected by immunocytochem- particularly susceptible to AGE transformation, such istry in renal biopsies. We compared the staining for as collagen, lens crystallins and DNA [8-10]. RAGE in nine patients with diabetic nephropathy, 20 In-vitro studies showed that AGEs can bind to with inflammatory and/or immune complex and 10 specific receptors on monocytes, macrophages, and with non-inflammatory renal diseases. Normal renal endothelial cells [11-13]. Binding to the cellular receptissue from seven patients with tumour nephrectomies tor elicits different, i.e. pleiotropic, responses, such as served as controls. release of cytokines, growth factors, induction of pro- - Results. In controls the only cells expressing RAGE coagulant reactions, binding of monocytes, increase in constitutively were interstitial cells and vascular permeability, alterations of the basement membrane smooth muscle cells (6/7), while distal tubular cells and quenching of NO [13-19]. These responses may were rarely positive (1/7). Endothelial cells of arteries/ be part of the pathomechanism leading to complicaarterioles, glomerular endothelial cells, podocytes, and tions of diabetes. It is also known that binding of capsular epithelial cells were consistently negative. AGEs to their binding sites leads to internalization In diabetic nephropathy, inflammatory and/or and degradation [20,21]. immune complex, and non-inflammatory renal diseases, all cell types mentioned above became positive for RAGE. Whilst the distribution of RAGE in the tissue was quite similar, staining intensity in inflammatory and/or immune complex diseases was higher than in diabetic nephropathy. The significance of receptor expression in vivo remains unknown. The binding site for AGEs on endothelial cells (RAGE) has been isolated and cloned [22-24]. Further studies showed that RAGE is expressed by endothelial cells, smooth muscle cells, and nerves in culture. In the cow a survey of different - Conclusion. RAGE induction in the kidney is not specific for diabetic nephropathy and occurs in other types of renal diseases as well.